Assessment of groundwater quality for drinking and irrigation in the Timahdite–Almis Guigou area (Middle Atlas, Morocco) - Samir Amrani; Said Hinaje; Mohamed El Fartati; Youssef Gharmane; Driss Yaagoub (Applied Water Science, 2022)
Abstract The groundwater in the Timahdite–Almis Guigou area flows through fluvio-lacustrine and volcanic formations of Plio-Quaternary age and Liassic limestone. The groundwater resources in this area are used for drinking water and irrigation of agricultural plots. 18 groundwater samples were collected for this study. The physico-chemical and bacteriological parameters analysed, such as temperature, electrical conductivity, pH, dissolved oxygen, Na+, K+, Ca2+, Mg2+, Cl−, HCO3 −, SO4 2−, NO2 −, NO3 −, faecal Coliforms, total Coliforms and faecal Streptococci, are used to characterise the quality of the groundwater and its suitability for drinking and for irrigation. The Piper and Gibbs diagrams and the saturation index were used to study the hydrogeochemical characteristics of groundwater. The quality of these was assessed on the basis of bacteriological quantification and water quality index (WQI) for drinking, and calculation of sodium percentage (Na%), sodium adsorption ratio (SAR) and permeability index (PI) for irrigation. The mineral saturation index in groundwater indicates that only carbonate minerals tend to precipitate, especially in the form of dolomite. On the other hand, the evaporative minerals are still undersaturated. The bacteriological quality and the water quality index (WQI) of this area are considered to be generally good to poor quality, with the exception of a few points, near the public dump of Almis Guigou, plateau of Lamrijate (Timahdite), Aït Hamza and Aït Ghanem, that show significant bacterial contamination and high concentrations of sodium, chlorides and nitrates. According to the calculation of the (Na%), the (SAR) and (PI), the groundwater samples are suitable for irrigation.